2018
DOI: 10.1063/1.5007760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan coating on the structural and magnetic properties of MnFe2O4 and Mn0.5Co0.5Fe2O4 nanoparticles

Abstract: We report the influence of polymer coatings on structural and magnetic properties of MnFe2O4 and Mn0.5Co0.5Fe2O4 nanoferrites synthesized by glycol thermal technique and then coated with chitosan viz. CHI-MnFe2O4 and CHI-Mn0.5Co0.5Fe2O4. The compounds were characterized by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), high-resolution scanning electron microscopy (HRSEM), Mössbauer spectroscopy and magnetization measurements. The powder XRD patterns of naked nanoferrites con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 16 publications
2
5
0
Order By: Relevance
“…The values obtained are 259 W/g for f = 327 kHz, H = 17 mT and 518 W/g for f = 981 kHz, H = 23 mT. These values are comparable with those reported for iron oxide nanoparticles [44,45]. The high specific absorption rate of the magnetic nanoparticles showed that the prepared nanoparticles have the potential to be used for practical therapy in targeted hyperthermia.…”
Section: Hyperthermia Studysupporting
confidence: 81%
“…The values obtained are 259 W/g for f = 327 kHz, H = 17 mT and 518 W/g for f = 981 kHz, H = 23 mT. These values are comparable with those reported for iron oxide nanoparticles [44,45]. The high specific absorption rate of the magnetic nanoparticles showed that the prepared nanoparticles have the potential to be used for practical therapy in targeted hyperthermia.…”
Section: Hyperthermia Studysupporting
confidence: 81%
“…XRD analysis further showed that all NPs were single phased, and no obvious changes were noted after the coating. It has previously been reported that polymer coating do not disrupt the phases [21,6] es [7]. FTIR spectra results confirmed the presence of functional groups in all the samples as seen in (Figure 1&2).…”
Section: Resultssupporting
confidence: 82%
“…An interesting peak is represented in the region of 900 cm-1 and is linked to the metal oxide vibrations i.e. Co-Fe and Ca-Fe [7].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aslibeiki et al [19] studied the polymer coated MnFe 2 O 4 nanoparticles and reported that the polymer coating enhanced the saturation magnetization, shifted blocking temperature towards the low temperature and changed strong super spin glass behavior to weak superparamagnetic state. Mdlalose et al [20] reported that chitosan coating reduced the M s value of MnFe 2 O 4 nanoparticles and enhanced H c . Therefore coating material can significantly alters the magnetic properties of nanoparticles which mainly depends upon the nature of the coating material.…”
Section: Introductionmentioning
confidence: 99%